Understanding microwave induced sorting of porphyry copper ores - John, R.S.; Batchelor, A.R.; Ivanov, D; Udoudo, O.B.; Jones, D.A.; Dodds, Chris; Kingman, S.W. (Elsevier, 2015)
Global demand for minerals and metals is increasing. It has been established that the impact of mining and mineral processing operations must be reduced to sustainably meet the demands of a low grade future. Successful incorporation of ore sorting in flow sheets has the potential to improve energy efficiency by rejecting non-economic material before grinding. Microwave heating combined with infra-red temperature measurement has been shown to distinguish low and high grade ore fragments from each other. In this work, experimentally validated 2-D finite difference models of a theoretical two phase ore, representing typical fragment textures and grades, are constructed. Microwave heating is applied at economically viable energy inputs and the resultant surface thermal profiles analysed up to 2 minutes after microwave heating. It is shown that the size and location of grains can dramatically alter surface temperature rise at short thermal measurement delay times and that the range of temperatures increases with increasing fragment grade. For the first time, it is suggested that increasing the delay time between microwave heating and thermal measurement can reduce the variation seen for fragments of the same grade but different textures, improving overall differentiation between high and low grade fragments.